A new target capture phylogeny elucidates the systematics and evolution of wing coupling in sack‐bearer moths. (15th January 2020) - St Laurent, Ryan A.; Mielke, Carlos G. C.; Herbin, Daniel; Dexter, Kelly M.; Kawahara, Akito Y.
Abstract: The frenulum is a wing coupling structure that is found on the wings of most families of Lepidoptera. It is a single bristle or set of bristles that originate from the base of the hindwing that often interlocks with the forewing during flight. This wing coupling mechanism is thought to have been a major evolutionary innovation that allowed for enhanced flight in Lepidoptera. The sack‐bearer moths (Mimallonidae) are unusual among Lepidoptera in that not all species within the family have a frenulum. We test the hypothesis that the frenulum is not necessary and is therefore lost in mimallonids that have longer male forewings, because such wings are perhaps better suited to be coupled by other means. To understand the evolution of the frenulum, we inferred the most taxonomically and genetically sampled anchored hybrid enrichment‐based phylogeny of Mimallonidae, including 604 loci from all 41 genera and from 120 species, covering about 40% of the described species in the family. The maximum likelihood tree robustly supports major relationships within the family, and ancestral state reconstruction clearly recovers the frenulum as the plesiomorphic condition in Mimallonidae. Our results show that the frenulum is more often observed in species that have shorter, rather than longer, male forewings. The frenulum has historically been used as an important character for intrafamilial classification in Mimallonidae, but our results conclusively show that this character system is more variable than previously thought. Based on our results, we erect two new subfamilies, Roelofinae St Laurent & Kawahara, subfam.n. and Meneviinae St Laurent, Herbin, & Kawahara, subfam.n., for four genera previously considered incertae sedis. In the predominantly frenulum‐lacking clade Cicinninae, we describe a new genus, Cerradocinnus St Laurent, Mielke, & Kawahara, gen.n., and the genus Gonogramma stat. rev. is revalidated to include many species previously placed in Cicinnus sensu lato. With these changes, Cicinnus can now be considered monophyletic. Thirty‐three species are transferred to Gonogramma from Cicinnus sensu lato. This published work has been registered on Zoobank, http://zoobank.org/urn:lsid:zoobank.org:pub:E33100E1‐DA6A‐4814‐A312‐36CBAA168B8B . Abstract : We inferred the most taxonomically and genetically sampled anchored hybrid enrichment‐based phylogeny of Mimallonidae, including 604 loci from all 41 genera, covering about 40% of the species in the family. Ancestral state reconstructions of frenulum presence/absence and statistical tests revealed that the frenulum is more often observed in species that have shorter, rather than longer, male forewings. We describe two new subfamilies for genera previously considered incertae sedis, describe a new genus, and revalidate Gonogramma to include many species formerly placed in Cicinnus .